PETROGRAPHY OF THE XENOLITHES FROM THE MALIN RAPAKIVI GRANITE MASSIF - HRUSHCHYNSKA, O.; MYTROKHYN, O.; BILAN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Authors investigated хenolithes within granitoids of Malin rapakivi massif located in south-east parts of multiple Korosten Pluton. It is established that biotite-amphibole and fayalite-pyroxene-amphibole granites of the main intrusive phases in Malin area contain numerous хenolithes of biotite gneisses and shales. The хenolithes of graphite-biotite gneisses and amphibole-biotite gneisses are less spread. Contact influence of granitoid magmas on хenolithes were displayed in formation of contact-thermal rocks of amphibole to pyroxene hornfels facies. It is concluded that investigated хenolithes belong to Teteriv group (PR1tt) which, possibly, were an old roof of Malin rapakivi massif.